Regulation of Social Hierarchy Over Time in Colonies of the Primitive Eusocial Wasp Mischocyttarus (Monocyttarus) cassununga. Von Ihering, 1903 (Hymenoptera, Vespidae) - Murakami, A. S. N. [UNESP]; Shima, S. N. [UNESP] (Kansas Entomological Soc, 2010)
Dominance behaviours among members of colonies of primitively eusocial wasps establish the social hierarchy, and are very important for the maintenance of social stability. The present work aimed at the factors involved in the social organization of colonies of Mischocyttarus (Monocyttarus) cassununga, during the post-emergence phase. Our results show that females at the top hierarchical positions are the most aggressive individuals in the colonies, sitting at the front of the comb, and that this stabilizes the social hierarchy. Actual violent competition for hierarchical positions was not observed, and the position of the queen was never challenged, the queen being relatively long-lived and active in socially controlling all the observed colonies. Therefore, we conclude that there are three main factors regulating social organization in this species: queen longevity, a stable linear hierarchy, and the constant control of the queen over the social organization of the colony.
Keywords: Mischocytarus cassununga; Polistinae; dominance; subordination; longevity